MASK: A Game-Based Learning Model for Developing Fundamental Movement Skills in Elementary Physical Education - Masleha Rasihati; Aprizal Fikri; Noviria Sukmawati; Muslimin; Dewi Septaliza (Jurnal Master Penjas & Olahraga, 2026)
This study aimed to develop the MASK learning model (Mengajar Ala Spinner dan Kartu) as an innovative instructional medium for improving fundamental movement skills among Phase C elementary school students. Employing a Research and Development approach with the ADDIE model, the study involved expert validation, small-scale field testing, and large-scale field testing across several public elementary schools in Gumay Ulu District, Lahat Regency. Data were collected through expert judgment, observation, and performance-based assessments. The results indicated that the MASK learning model met acceptable validity criteria and demonstrated practical feasibility in classroom implementation. Findings from both small- and large-scale trials showed that most students achieved good to very good performance levels in locomotor, non-locomotor, and manipulative skills, accompanied by increased engagement and motivation during learning activities. These results suggest that the MASK learning model constitutes a valid and effective instructional alternative for elementary Physical Education learning grounded in physical literacy principles.